Python : Advanced Predictive Analytics : Gain practical insights by exploiting data in your business to build advanced predictive modeling applications /: Advanced Predictive Analytics : Gain practical insights by exploiting data in your business to build advanced predictive modeling applications. (2017) - J, Joseph; (Data scientist), Kumar, Ashish
No abstract available